2010
DOI: 10.2174/1874421401004010132
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomatid-Encoded Inhibitors of Peptidases: Unique Structural Features and Possible Roles as Virulence Factors

Abstract: Trypanosomatids rely on peptidases as potent virulence factors and were recently found to contain a unique set of natural peptidase inhibitors not found in higher eukaryotes or in yeast, but present in a limited number of bacteria. Chagasin, identified in Trypanosoma cruzi, is a tight-binding, high affinity inhibitor of papain-like cysteine peptidases that has an Ig-like fold and inactivates target enzymes through a limited number of contacts mediated by a few conserved residues on three exposed loops. Chagasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…However, the presence of an inhibitor of serine peptidases is limited to trypanosomes including Leishmania spp. [10]. It is reported that ~50–80% of the parasites are killed by trypsin during the early blood meal digestion [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of an inhibitor of serine peptidases is limited to trypanosomes including Leishmania spp. [10]. It is reported that ~50–80% of the parasites are killed by trypsin during the early blood meal digestion [29].…”
Section: Discussionmentioning
confidence: 99%
“…for the protection against the proteolytic activities of the peptidases and to regulate their function. Some of the natural inhibitors of serine peptidases (ISP) are reportedly present in different trypanosomatids such as ISP1 ( Trypanosoma brucei brucei , Leishmania major ), ISP2 ( Trypanosoma cruzi , Trypanosoma brucei rhodesiense , L. major ) and ISP3 ( L. major ) [10, 11]. The presence of LdISP has also been recently reported in L. donovani [12].…”
Section: Introductionmentioning
confidence: 99%